The influence of sport motivation on college students’ subjective exercise experience: a mediation model with moderation - Liu, Fengbo; Li, Ning (Frontiers in Psychology, 2023)
Background The degree to which an individual experiences a positive emotional state after exercise is a measurement of how much enjoyment sports bring to the individual. This can also be seen as the individual’s essential motivation for engaging in sports, and an indirect means of improving the individual’s physical health. Therefore, it is necessary to explore the factors that affect college students’ subjective exercise experience and their effecting mechanism, thereby providing a basis for promoting college students’ positive emotional experience after exercise. Methods A questionnaire survey on 600 college students was conducted to examine the mediating effect of sport-confidence on the relationship between college students’ sport motivation and their subjective exercise experience, and to investigate whether this process is moderated by the feelings of inadequacy. Results The indirect effect of sport-confidence was significant (95% CI [0.133, 0.276]), and the index of moderated mediation Bootstrap 95% CI [0.003, 0.017] did not contain 0. Conclusion The results indicated that: (1) sport-confidence had a partial mediating effect between college students’ sport motivation and their subjective exercise experience; (2) the mediating effect of sport-confidence was moderated by the feelings of inadequacy, and the feelings of inadequacy moderated the latter half path of the mediating process of sport motivation - sport-confidence - subjective exercise experience. Therefore, the influence of college students’ sport motivation on their subjective exercise experience is a moderated mediating model.